2015
DOI: 10.1039/c5ob00200a
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalysed cross-coupling: an untapped potential

Abstract: Copper is emerging as a viable catalytic metal for cross-coupling reactions to construct carbon-carbon (C-C) bonds. Recent revelations that Cu-catalysts can execute with high efficacy the cross-couplings of a variety of organometallic reagents, including organomagnesium, organoboron, organosilicon, organoindium and organomanganese, with alkyl, aryl and heteroaryl halides clearly demonstrate the versatility of Cu-based catalytic systems in conducting these reactions. In addition, Cu-catalysts are exhibiting a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(80 citation statements)
references
References 170 publications
2
76
0
2
Order By: Relevance
“…[12] Althoughc opperc atalysis of severalc ross-coupling reactions is well established, few examples of its use in Suzuki-Miyaura reactions have been described. [52] Among them, problematic dipolar aprotic solvents such as DMF and elevated temperatures are oftentimes required. [53] Av ery mild alternative has been documented wherein ppm levelso fp alladium serve as co-catalyst in TPGS-750-M/H 2 Oa t4 5 8C( Scheme27).…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
“…[12] Althoughc opperc atalysis of severalc ross-coupling reactions is well established, few examples of its use in Suzuki-Miyaura reactions have been described. [52] Among them, problematic dipolar aprotic solvents such as DMF and elevated temperatures are oftentimes required. [53] Av ery mild alternative has been documented wherein ppm levelso fp alladium serve as co-catalyst in TPGS-750-M/H 2 Oa t4 5 8C( Scheme27).…”
Section: New Cu Chemistry In Watermentioning
confidence: 99%
“…Cu-promoted cross-couplings are emerging as a viable alternative to precious metal-catalyzed processes. 12 While Cucatalyzed couplings of aminoboronates have not previously been described, observations made during the course of this work point toward a likely mechanism for the arylation reaction. First, complete racemization of enantioenriched aminoboronate 3a occurred in formation of product 2a, suggesting that a configurationally unstable intermediate formed during the reaction (eq 1).…”
mentioning
confidence: 92%
“…The pyrrolo [2,3-d ]pyrimidine derivatives were prepared in moderate yield by using Pd. Recently, Cu-catalyzed coupling reactions devoted to the efficient synthesis of heterocycles have acquired increasing attention, and displayed lower cost/toxicity of Cu sources, mild conditions, and broad substrate scope (19)(20)(21)(22)(23). Ma et al reported the first Cu/6-methylpicolinic acid catalyzed synthesis of pyrrolo [2,3-d]pyrimidine derivatives in moderate to excellent yields from substituted 5-bromopyrimidin-4-amines and alkynes (24).…”
Section: Resultsmentioning
confidence: 99%